P–092 The more, the merrier: does ejaculatory frequency influence seminal parameters in oligospermic men?. (6th August 2021) - Massarotti, C; Maccarini, E; Loberti, L; Leo, C D; Stigliani, S; Scaruffi, P; Anserini, P
Abstract: Study question: Does ejaculatory frequency during the three months preceding semen collection influence semen parameters in oligospermic men? Summary answer: A frequency of 2–3 ejaculations/week during the three months preceding semen collection significantly optimizes sperm motility, without any reduction in sperm concentration. What is known already: Male gametes undergo crucial physiological and biochemical changes during epididymal transit, but a longer storage is known to have negative effects on semen quality, especially on motility. Previous studies focused on abstinence prior to semen collection, while few data are available on the effect of ejaculation frequency. On one hand, a longer storage could increase exposure to reactive oxygen species and a pro-inflammatory environment, with a reduction in vitality and motility. On the other, an increased ejaculation frequency could cause a reduction in sperm volume and concentration. The effects of ejaculatory frequency are particularly understudied in men with oligospermia. Study design, size, duration: This is a retrospective study performed at a tertiary level public infertility center. We included all semen samples, collected both for diagnostic purposes and ART cycles between September 2019 and September 2020, with a sperm concentration of 15 million/ml or less, and an abstinence of 3- 5 days. Exclusion criteria were surgically collected or collected for fertility preservation semen samples. Participants/materials, setting, methods: Standard demographic and clinical data were recorded, as well as semen parameters. Ejaculation frequency was considered "optimal" (at least 2–3/week) or "reduced" (<1/week). The potential predictive role of ejaculation frequency, age, BMI, smoking habits, previous cryptorchidism, varicocele, days of abstinence on semen parameters was evaluated by univariate and then by multivariate analysis for all factors significant in the univariate models. P < 0.05 was considered statistically significant. Main results and the role of chance: Out of 738 men, 491 reported an optimal ejaculation frequency, 247 had <1 ejaculation/week, no one reported everyday ejaculations. Total sperm mobility (35.91±22.84% vs. 32.28±16.91%, p = 0.02) and sperm rapid progressive motility (5.56±6.09% vs. 4.20±6.1%, p = 0.006) were significantly higher in the group with optimal ejaculation frequency. Ejaculation frequency remained predictive of total mobility (p = 0.04) and rapid progressive mobility (p = 0.03) in a multivariate linear regression model with age and sperm concentration. Sperm volume (2.92±1.56 ml vs. 2.91±1.54 ml, p=NS) and concentration (5.74±5.05 mil/ml vs. 6.05±4.78 mil/ml, p=NS) did not significantly differ depending on the declared ejaculation frequency. Limitations, reasons for caution: The study is retrospective and ejaculatory frequency was self-reported as an estimate of the mean of the number of ejaculations per week. Wider implications of the findings: Optimizing ejaculatory frequency may improve ART outcomes as well as success of spontaneous conceptions. There is no reason to limit ejaculatory frequency in oligospermic men for a hypothesized benefic in sperm concentration. Trial registration number: Not applicable